2021
DOI: 10.3389/fphar.2021.614442
|View full text |Cite
|
Sign up to set email alerts
|

Alnus hirsuta (Spach) Rupr. Attenuates Airway Inflammation and Mucus Overproduction in a Murine Model of Ovalbumin-Challenged Asthma

Abstract: Alnus hirsuta (Spach) Rupr. (AH), a member of the Betulaceae family, is widely used in Eastern Asia of as a source of medicinal compounds for the treatment of hemorrhage, diarrhea, and alcoholism. In this study, we investigated the protective effects of a methanolic extract of AH branches against airway inflammation and mucus production in tumor necrosis factor (TNF)-α-stimulated NCI-H292 cells and in an ovalbumin (OVA)-challenged allergic asthma mouse model. Female BALB/c mice were injected with OVA (40 μg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In addition, PLS-DA showed that peaks 5, 6, 10 (vernine), 12 (5-hydroxymethylfurfural), 14 (tryptophan) and 15 (adenosine) in the fingerprints were closely related to the inhibitory effect on MUC5AC mucin production, and could provide pharmacodynamic evaluation indicators for resolving the phlegm effect of PRPCA. NCI-H292 cells, a human airway mucussecreting epithelial cell line, provide a model system for studying lung and bronchial mucus hypersecretion diseases [14,15]. LPS stimulation significantly increases the expression of mucin in NCI-H292 cells, which can be used in the preparation of mucus hypersecretion models to evaluate its inhibitory effect on mucin production [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PLS-DA showed that peaks 5, 6, 10 (vernine), 12 (5-hydroxymethylfurfural), 14 (tryptophan) and 15 (adenosine) in the fingerprints were closely related to the inhibitory effect on MUC5AC mucin production, and could provide pharmacodynamic evaluation indicators for resolving the phlegm effect of PRPCA. NCI-H292 cells, a human airway mucussecreting epithelial cell line, provide a model system for studying lung and bronchial mucus hypersecretion diseases [14,15]. LPS stimulation significantly increases the expression of mucin in NCI-H292 cells, which can be used in the preparation of mucus hypersecretion models to evaluate its inhibitory effect on mucin production [16].…”
Section: Discussionmentioning
confidence: 99%
“…(3), tyrosine (4), uracil (7), adenine (8), inosine (9), vernine (10), 5hydroxymethylfurfural (12), tryptophan (14), and adenosine (15). The similarity values and common peak areas of 20 PRPCA batches are presented in Tables 1 and 2, respectively.…”
Section: Similarity Analysis Of Hplc Fingerprintsmentioning
confidence: 99%
“…Sensitization 20 : Mice, except those in the sham group (receiving an equal volume of phosphate‐buffered saline [PBS]), were injected intraperitoneally with 40 μg of OVA (O1641, Sigma) and 2 mg PBS (Hyclone) containing 10% aluminum hydroxide (Aladdin) on Days 0, 7, and 14.…”
Section: Methodsmentioning
confidence: 99%
“…In Eastern Asia, alcoholism, diarrhea, and hemorrhage are treated with compounds derived from this member of the Betulaceae family. Using an ovalbumin-induced murine asthma model to compare Alnus hirsuta with dexamethasone (3 mg/kg), Lee et al found that this plant alleviates mucus overproduction and airway infammation at the concentration of 50 mg/kg [153].…”
Section: Alnus Hirsuta (Spach)mentioning
confidence: 99%